Evaluasi Kapasitas Lahan Parkir Wisata Kuliner Kerkof Garut - Elgi Ilman Maldini; Athaya Zhafirah (Jurnal Konstruksi, 2024)
Parking areas are one of the transportation infrastructures that must be well organized and managed in order to meet the need for adequate and appropriate parking spaces. The problem that occurs at Kerkof Culinary Tourism on weekends is that the parking requirements for two-wheeled vehicles exceed capacity, resulting in four-wheeled vehicles being parked on the road and causing traffic jams. This research aims to evaluate the capacity of motorized vehicle parking in the Kerkof Culinary Tourism area. The method used was a direct survey of the number and duration of parked vehicles at the research location as well as an analysis of parking needs. The analysis results show that the parking capacity for two-wheeled vehicles covering an area of ”‹”‹486 m2 for current conditions is 324 SRP with a parking index of more than 100%. This indicates that the parking area in the Kerkof Culinary Tourism area is no longer able to accommodate the demand for parking for two-wheeled vehicles. So an evaluation was carried out with the results of the need for two-wheeled vehicle parking area of ”‹”‹958.5 m2 with 639 SRP.